Physician Knowledge and Training as Determinants of Informed Consent Implementation: A Cross-Sectional Study in Two Indonesian Hospitals - Putrihamidah, Diyanthie Aulia; Adhayati, Baety; Louisa, Melva (Journal of Health and Nutrition Research, 2025)
This study aims to analyze the relationship between physicians’ knowledge of informed consent and the completeness of its implementation in medical procedures. The research employed an observational analytic approach with a cross-sectional design and quantitative methods. The study population consisted of general practitioners, specialists, dentists, and dental specialists working at Banten Provincial General Hospital and Dr. Drajat Prawiranegara Regional General Hospital. A total of 94 physicians were included as respondents. The variables examined included physicians’ knowledge of informed consent, the completeness of its implementation, and respondent characteristics such as age, years of service, and training history. Data were analyzed using the chi-square test with a significance level of p < 0.05. The results indicated a significant association between physicians’ knowledge, years of service, and prior training with the completeness of informed consent implementation. Physicians with good knowledge demonstrated a higher likelihood of complete implementation (OR 10.6; 95% CI 3.7–30.4) compared to those with poorer knowledge. Similarly, physicians with less than five years of service had a higher rate of complete informed consent implementation (78%) compared to those with five or more years of service (57.1%). Moreover, those who had received training were significantly more likely to implement informed consent completely (OR 6.95; 95% CI 1.51-31.94) than those without training experience. In contrast, physician age was not significantly associated with informed consent completeness. In conclusion, enhancing physician knowledge and promoting ongoing training are essential to improving the quality of informed consent practices in clinical settings.